Initial results from a driving safety survey distributed to ambulance paramedics in Qatar - Guillaume Alinier (6952004) (2015)
Fatal vehicle crashes are not uncommon for ambulance paramedics (1-3). Emergency services staff may be overconfident and overestimate the privileges they have on the road and overlook basic driving safety principles (4). In line with the WHO (5) a driving safety campaign targeting some 935 registered HMCAS drivers and other staff was initiated in June 2015. We aim to determine if our approach is effective in changing behaviour and believes, and reducing the number of accidents in which our vehicles are involved, and surveyed the staff. Posters and stickers were designed with respectively 6 and 4 key messages covering the most frequent issues resulting in collisions (with objects/other vehicles) or potentially putting lives at risk. These are visibly displayed at all ambulance stations and in the vehicle driving compartments. An official staff circular was then sent to inform them of the campaign. A month later a survey accessible online and on paper started to be distributed to staff. In one month 141 anonymous questionnaires were returned fully completed. On average using a 5-point Likert scale respondents rated themselves as being safe drivers (4.2/5) and estimated the monthly number of accident with HMCAS vehicles to be 15.3 (22.1/month registered in 2014) and to mainly occur at traffic light (75.2%). 75% had noticed the posters and 60% the stickers. Those who noticed could respectively cite 53.3% (3.2) and 54.6% (2.2) of the key messages. 72% of respondents (n=102) had an HMCAS driving qualification (10.9% of qualified HMCAS drivers). On average they had been involved in 0.95 accident requiring vehicle repair. As expected, staff underestimate the number of accidents. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.59